2001
DOI: 10.1002/bit.1091
|View full text |Cite
|
Sign up to set email alerts
|

Role of organic solvents on Pa‐hydroxynitrile lyase interfacial activity and stability

Abstract: Catalytic activity and adsorption of Pa-hydroxynitrile lyase (Pa-Hnl) was investigated at various organic solvent/water interfaces. We focused on the role of solvent polarity in promoting activity and stability in two-phase systems, specifically for the solvents heptane, dibutyl ether (DBE), diisopropyl ether (DIPE), butylmethyl ether (BME), and methyl tert-butyl ether (MTBE). Enzyme activity towards mandelonitrile cleavage was determined in a recycle reactor with a well-defined interfacial area as described b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
38
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 17 publications
8
38
1
Order By: Relevance
“…After enzyme had been washed out of the aqueous phase in a biphasic reactor, Hickel et al (2001) showed that 0-30% of the original reaction rate was found back in the reactor. This does not prove, however, that originally more than 30% of the reaction occurred at the interface.…”
Section: Each Curve Inmentioning
confidence: 99%
See 3 more Smart Citations
“…After enzyme had been washed out of the aqueous phase in a biphasic reactor, Hickel et al (2001) showed that 0-30% of the original reaction rate was found back in the reactor. This does not prove, however, that originally more than 30% of the reaction occurred at the interface.…”
Section: Each Curve Inmentioning
confidence: 99%
“…The preceding discussion shows that the PaHNLcatalyzed reaction in a biphasic liquid has been interpreted as mass-transfer limited (Willeman et al, 2002a) but also in terms of interfacial enzyme adsorption (Hickel et al, 1999(Hickel et al, , 2001. Quantitative comparison of the conditions of these authors is difficult so far.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition to reiterating the original supporting data for this conclusion (Hickel et al, 1999), we provide further experimental evidence from a recent study on the role of solvents in biphasic pa-Hnl catalysis (Hickel et al, 2001). We also adopt the aqueous-phase homogeneousreaction picture of Willeman et al (2002) and demonstrate that such a model does not reproduce our experimental findings.…”
Section: Introductionmentioning
confidence: 56%